The Role of Teachers in Shaping Responsible Character Answers Students in Elementary School: Systematic Literature Review - Weni Soraya; Elizar; Eny Munisah; Berta Apriza (Universitas Pendidikan Ganesha, 2026)
Character education in elementary schools remains a critical issue, particularly in fostering students’ responsibility as a fundamental value for their personal and social development. However, the implementation of responsibility character education is often not carried out optimally due to the lack of systematic strategies and consistent teacher involvement in the learning process. This study aims to analyze and synthesize the role of teachers in shaping students’ responsibility character through a Systematic Literature Review (SLR) approach. The study involved 10 selected articles published in accredited scientific journals within the 2021–2025 period, obtained through systematic searching using relevant keywords. Data were collected through documentation techniques and analyzed using qualitative content analysis to identify patterns, themes, and conceptual relationships related to teachers’ roles in character education. The findings reveal that teachers play multidimensional roles as role models, facilitators, motivators, and guides in internalizing responsibility values through modeling behavior, habituation practices, integration into classroom instruction, and extracurricular activities. The study also highlights that the effectiveness of character formation is strengthened by the synergy between school environments and parental involvement. Conceptually, this study emphasizes that consistent and reflective teacher engagement, supported by a positive educational environment, contributes significantly to the development of responsible character in students. These findings provide important implications for designing sustainable character education strategies that are integrative, contextual, and applicable in elementary education settings.